2019
DOI: 10.1002/prep.201900249
|View full text |Cite
|
Sign up to set email alerts
|

Hot Spot Chemistry in Several Polymer‐Bound Explosives under Nanosecond Shock Conditions

Abstract: Initial hot spot temperatures and temperature evolutions for 4 polymer‐bound explosives under shock compression by laser‐driven flyer plates at speeds from 1.5–4.5 km s−1 are presented. A new averaging routine allows for improved signal to noise in shock compressed impactor experiments and yields temperature dynamics which are more accurate than has been previously available. The PBX formulations studied here consist of either pentaerythritol tetranitrate (PETN), 1,3,5‐trinitro‐1,3,5‐triazinane (RDX), 2,4,6‐tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…A HMX PBX was synthesized using previously detailed procedures and consisted of 80% HMX and 20% Sylgard 182 binder. ,,,, These samples had a 96.1% theoretical maximum density and an average particle size of 30 ± 27 μm (SI, Section II). PBX charges were 1 mm in diameter and 40 μm thick.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…A HMX PBX was synthesized using previously detailed procedures and consisted of 80% HMX and 20% Sylgard 182 binder. ,,,, These samples had a 96.1% theoretical maximum density and an average particle size of 30 ± 27 μm (SI, Section II). PBX charges were 1 mm in diameter and 40 μm thick.…”
Section: Methodsmentioning
confidence: 99%
“…The formulas for temperature calculations and additional information over the averaging algorithm are found in SI, Section IV. The original pyrometer probed a region of less than 100 μm at the center of the flyer plate. ,,, For the present study, we modified the optical path (Figure S4) so the pyrometer observed the entire region surrounding the shocked HMX, about 400 μm in diameter.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations